Plasmin Is a Specific Stimulus of the 5-Lipoxygenase Pathway of Human Peripheral Monocytes - Weide, Ingo; Tippler, Bettina; Syrovets, Tatjana; Simmet, Thomas (Thrombosis and Haemostasis, 1996)
The objective of this study was to characterize the plasmin-induced stimulation of leukotriene (LT) B4 biosynthesis in human peripheral monocytes (PM). Plasmin up to 175 × 10-3 CTA U/ml triggers a concentration-dependent release of 5-lipoxygenase-derived LTB4 while release of the cyclooxygenase products thromboxane (TX) B2 and prostaglandin (PG) E2 remained unaffected. The stimulatory effect appeared to be specific in as much as 1) it was found in PM, but not in polymorphonuclear neutrophils (PMN), 2) it requires the lysine binding sites of plasmin molecule since it was inhibited by the lysine analogues 6-aminohexanoic acid (6-AHA) and trans-4(aminometh-yl)cyclohexane-l-carboxylic acid (t-AMCA), 3) the intact catalytic center of plasmin is required since neither plasminogen nor catalytic center-blocked plasmin share the stimulatory effect of active plasmin, 4) other serine proteases such as a-chymotrypsin, human neutrophil elastase and cathepsin G did not stimulate release of detectable amounts of LTB4 from PM. In addition, catalytic center-blocked plasmin antagonized the stimulatory effect of active plasmin. Plasmin-mediated monocyte activation apparently proceeds via a pertussis toxin-sensitive G protein. Plasmin did not increase inositol (1,4,5) trisphosphate levels, but a time- and concentration-dependent stimulation of cyclic GMP formation was observed. The data show that plasmin is a specific stimulus for human peripheral monocytes. Plasmin may be an important link between the coagulation cascade and inflammatory reactions.